Un aparato teórico para el análisis de las representaciones de lo público en jóvenes universitarios. (2010)
The article presents the theoretical and methodological approaches that guide the research entitled "An approach to social representations of public issues in students of the University Los Libertadores; through their interpretation of images"; advanced in 2010. It presents philosophical and sociological conceptions of the public sphere as a general frame of reference and contrast for the investigation. It is proposed heuristically a topology of the public sphere; to visualize their locations and levels of constitution. Tackling the question of the constitution of the public sphere some observations are made about the role played by communication technologies. Finally; we make explicit the methodological elements to be used in this qualitative investigation: the theory of social representations; with the specific technique of images interpretation.